Scalp-Ear-Nipple syndrome: first report of a Potassium channel tetramerization domain-containing 1 in-frame insertion and review of the literature. Issue 4 (26th August 2021) - Butler, Kameryn M.; Bahrambeigi, Vahid; Merrihew, Allie; Friez, Michael J.; Cathey, Sara S.
Abstract : Objectives: Pathogenic missense variants in the potassium channel tetramerization domain-containing 1 ( KCTD1 ) gene are associated with autosomal dominant Scalp-Ear-Nipple syndrome (SENS), a type of ectodermal dysplasia characterized by aplasia cutis congenita of the scalp, hairless posterior scalp nodules, absent or rudimentary nipples, breast aplasia and external ear anomalies. We report a child with clinical features of an ectodermal dysplasia, including sparse hair, dysmorphic facial features, absent nipples, 2–3 toe syndactyly, mild atopic dermatitis and small cupped ears with overfolded helices. We also review the published cases of SENS with molecularly confirmed KCTD1 variants. Methods and results: Using whole-exome sequencing, we identified a novel, de novo in-frame insertion in the broad-complex, tramtrack and bric-a-brac (BTB) domain of the KCTD1 gene. By comparing to the previously reported patients, we found that our patient's clinical features and molecular variant are consistent with a diagnosis of SENS. Conclusions: This is only the 13th KCTD1 variant described and the first report of an in-frame insertion causing clinical features, expanding the mutational spectrum of KCTD1 and SENS.